Primary Carcinosarcoma of the Spleen: A Rare Case Report of Incidental Finding after Splenic Trauma - Hugues Ndasu Matendo; Raouf Fayisall Geraldo; Liviu Musteata; Joel Allan Green; Valeriu Krasovski; Valentin Nitu; Thierry Gastaud; Fabrice Cattan (Case Reports in Surgery)
Primary carcinosarcoma of the spleen is a rare, aggressive splenic malignancy. To date, seven cases have been reported in the literature. We report a first case of primary carcinosarcoma of the spleen in France. A 75-year-old woman with a medical history of hysterectomy for uterine adenocarcinoma presented with left hypochondrium pain following blunt abdominal trauma. A splenic mass was noted on computed tomography (CT) scan. A splenectomy was performed by laparotomy. Histology revealed a malignant mixed Mullerian tumor. The PET scan allowed us to confirm that it was a primary lesion of the spleen. She is currently undergoing adjuvant chemotherapy despite the tumor progression. The interest of this case lies in the rarity of primary carcinosarcomas of the spleen and the circumstances of its diagnosis.